GLOBAL RECESSION AND ASIAN GROWTH: EXPERIENCE AND PROSPECTS - Dowling, John Malcolm (Journal of Indonesian Economy and Business, 2009)
The paper outlines current macroeconomic developments in industrial countries and explains how slower growth in these economies is being transmitted to developing economies in Asia. The macroeconomic outlook for industrial countries in 2009 is discussed along with the transmission mechanism that has brought the global downturn tothe Asian economies. Monetary and fiscal policy adjustments in Asian economies have been implemented to address the downturn in economic activity and these policies are discussed in some depth. All the major countries in East Asia, Southeast Asia and South Asia are analysed. The paper concludes with a brief review of the outlook for 2010.Keywords: global recession, monetary and fiscal policy, Asian economies, economic outlook.